WIPI-1 Positive Autophagosome-Like Vesicles Entrap Pathogenic Staphylococcus aureus for Lysosomal Degradation. (9th July 2012) - Mauthe, Mario; Yu, Wenqi; Krut, Oleg; Krönke, Martin; Götz, Friedrich; Robenek, Horst; Proikas-Cezanne, Tassula
Abstract : Invading pathogens provoke the autophagic machinery and, in a process termed xenophagy, the host cell survives because autophagy is employed as a safeguard for pathogens that escaped phagosomes. However, some pathogens can manipulate the autophagic pathway and replicate within the niche of generated autophagosome-like vesicles. By automated fluorescence-based high content analyses, we demonstrate that Staphylococcus aureus strains (USA300, HG001, SA113) stimulate autophagy and become entrapped in intracellular PtdIns(3)P-enriched vesicles that are decorated with human WIPI-1, an essential PtdIns(3)P effector of canonical autophagy and membrane protein of both phagophores and autophagosomes. Further, agr -positive S. aureus (USA300, HG001) strains were more efficiently entrapped in WIPI-1 positive autophagosome-like vesicles when compared to agr -negative cells (SA113). By confocal and electron microscopy we provide evidence that single- and multiple-Staphylococci entrapped undergo cell division. Moreover, the number of WIPI-1 positive autophagosome-like vesicles entrapping Staphylococci significantly increased upon (i) lysosomal inhibition by bafilomycin A1 and (ii) blocking PIKfyve-mediated PtdIns(3, 5)P2 generation by YM201636. In summary, our results provide evidence that the PtdIns(3)P effector function of WIPI-1 is utilized during xenophagy of Staphylococcus aureus . We suggest that invading S. aureus cells become entrapped in autophagosome-like WIPI-1 positive vesicles targeted for lysosomal degradation in nonprofessional host cells.